1965
DOI: 10.1113/jphysiol.1965.sp007601
|View full text |Cite
|
Sign up to set email alerts
|

The release of acetylcholine into the cerebral subarachnoid space of anaesthetized cats

Abstract: The present experiments on anaesthetized cats show that acetylcholine is released from the ventral surface of the brain. The results were obtained by perfusing the subarachnoid space with neostigmine, either from cisterna magna to fissures of Sylvius or from interpeduncular fossa to cisterna magna, and assaying the acetylcholine in the effluent.Release of acetylcholine from the surface of the brain has previously been studied only from the dorsal and lateral aspects of the cerebral cortex, and the technique us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1

Year Published

1965
1965
1979
1979

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 6 publications
1
8
1
Order By: Relevance
“…There is a considerable amount of evidence that this is so. Morphine reduces acetylcholine release in the isolated guinea-pig ileum (Paton, 1957;Schaumann, 1957) and in the brain Beleslin, Polak & Sproull, 1965) and the results presented in this paper are consonant with the view that, after morphine administration, acetylcholine release is reduced by a direct action of the drug rather than as a simple consequence of reduced neuronal activity. The effects of nalorphine are particularly interesting in this connection.…”
Section: Discussionsupporting
confidence: 89%
“…There is a considerable amount of evidence that this is so. Morphine reduces acetylcholine release in the isolated guinea-pig ileum (Paton, 1957;Schaumann, 1957) and in the brain Beleslin, Polak & Sproull, 1965) and the results presented in this paper are consonant with the view that, after morphine administration, acetylcholine release is reduced by a direct action of the drug rather than as a simple consequence of reduced neuronal activity. The effects of nalorphine are particularly interesting in this connection.…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that morphine depressed the release of acetylcholine not only in iso lated guinea pig ileum (23,24) but also in the cat brain (25)(26)(27)(28). However, the recurrent inhibition via Renshaw cell arcs, relevant transmitter being considered as acetylcholine (29), was almost unchanged in our experiment by either morphine (5 mg/kg) or fentanyl (401ig/kg).…”
Section: Discussioncontrasting
confidence: 46%
“…As the acetylcholine which enters the anterior horn is mainly derived from the caudate nucleus (Beleslin, Carmichael & Feldberg, 1964) the effect of morphine must be mainly on this structure. However, in experiments carried out with Dr D. H. Sproull (Beleslin, Polak & Sproull, 1965) we have found that morphine apparently has a similar effect on the cerebral cortex since it reduces the acetylcholine output into the perfused subarachnoid space. So the effect appears to be a more general one and not confined to a particular part of the brain.…”
Section: Discussionmentioning
confidence: 87%